Kaitan Intesitas Kerja dengan Kondisi Stress Pada Karyawan: Kaitan Intesitas Kerja dengan Kondisi Stress Pada Karyawan - Darmawan, Ardhian; Setyaningrum, Niken; Triasa Firdausy, Shafira (Jurnal Kesehatan Masa Depan, 2023)
Background: The development of the industrial era was based on increasing community needs. Increasing consumer demand makes companies increase the amount of production which risks increasing the intensity of company activity. Increased activity by the company influences its human resources, namely the company's employees. The intensity of exercise which tends to increase has the potential to have a fatigue effect on employees. Work fatigue impacts decreasing work performance and the body's physical endurance to continue completing work. The National Safety Council reports that 13% of workplace injuries are related to fatigue. Around 2,000 workers have had accidents, indicating that 97% have at least one risk factor for fatigue at work, while more than 80% have more than one risk factor (RI Ministry of Health, 2022). In 2021, the number of work accidents in Indonesia will be 234,270 cases. This number increased by 5.65% from the previous year which amounted to 221,740 cases. The condition of fatigue experienced by employees has the potential to cause distress for employees. Disturbed psychological conditions have an impact on physical conditions. Methods: This research is a descriptive study with a cross-sectional approach. The number of samples is 131 respondents. The research instrument used the Subjective Self Rating Test (SSRT) Questionnaire prepared by the Industrial Fatigue Research Committee and the Health and Safety Executive Questionnaire. Testing the research data using the Kendall Tau data test. Results: Based on the results of the Kendall-Tau correlation test, it is known that the significance value (2-tailed) between work fatigue and work stress is 0.000 <0.05, it is concluded that there is a significant (real) relationship between work intensity and work stress conditions Keywords: Work Intensity; Work Stress